Estimating the IAF of coffee from the volume occupied by leaves and plant architecture - Barbosa, João Paulo Rodrigues Alves Delfino; Martins, Giordane Augusto; Ferreira, Rafael Teixeira; Pennacchi, João Paulo; Souza, Vinícius Fernandes de; Soares, Angela Maria (Coffee Science - ISSN 1984-3909, 2012)
The methods used for estimating the leaf area index (LAI) of coffee (Coffea arabica L.) show limitations related to therepresentation of some aspects of coffee crops, affecting the LAI in time and space. This work was developed to propose a method forassessing the LAI of coffee aiming to reduce those limitations. We studied plants in the production phase of the Mundo Novo and Catuaívarieties, in plantations located in Lavras-MG, during the dry season and rainy season from 2010 to 2011. The height, total length ofprimary branches, the length of the region without leaves in the canopy and the LAI of those plants were evaluated. These data wereused to estimate the volume occupied by leaves and, subsequently, to obtain equations that describe the behavior of LAI in relation tothis volume. There were three equations that described the LAI variations in relation to the volume occupied by leaves: linear,expolinear and seasonal. These three models showed realistic estimates when applied to plants from plantations located in TrêsPontas-MG. Potentially, this method can be applied for estimating the LAI of a plant or canopies. It has the advantage of a morerealistic representation of the shape of the plant in time and space compared to similar methods. With the proposed method is expectedto meet the demands of productivity forecasting models for coffee, reducing the limitations observed in the commonly used methods forLAI determination.